The influence of executive functions on phonological awareness skills in 2nd year schools (Research, Society and Development, 2020)
The aim of this study is to analyze the influence of executive function on the performance of phonological awareness skills tasks of children in the second grade of elementary school in two schools of municipal public school. 18 children aged 7 years of both genders, enrolled in the second grade of public elementary school, participated in the study. Evaluations of executive functions and phonological awareness were performed. Pearson correlation statistic and Fischer's exact test were used, with significance level p